Food Antibodies in Serum—A Screening Test for Coeliac Disease. Issue 254 (August 1972) - Carswell, F.; Ferguson, A.
Abstract : Food antibody tests were performed on the sera of 52 children undergoing investigation for suspected coeliac disease. 30 of these were subsequently shown to have coeliac disease. The food antibody tests were at least as effective a screening test for coeliac disease as the whole blood folate determination, serum immunoglobulins, or the barium meal and follow-through.